Measuring the Impact of Oral Health on Quality of Life in Britain Using OHQoL-UK(W) - Colman McGrath, BA, BDentSc, DDPHRCS, MSc, FDSRCS, FFDRCSI, PhD; Raman Bedi, BDS, MSc, (Blackwell Synergy, 2003)
This study assessed the impact of oral health on quality of life (OHQoL) in Britain and identified disparities in OHQoL among subgroups of the population